Optimal interest rate stabilization in a basic sticky-price model - Matthias Paustian; Christian Stoltenberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper studies optimal monetary policy with the nominal interest rate as the single policy instrument in an economy,where firms set prices in a staggered way without indexation and real money balances contribute separately to households'utility. The optimal deterministic steady state under commitment is the Friedman rule - even of the importance assigned to the utility of money is small relative to consumption and leisure. We approximate the model around the optimal steady state as the long-run policy target. Optimal monetary policy is characterized by stabilization of the nominal interest rate instead of inflation stabilization as the predominant principle.
Keywords: E32; E52; E58; 330; Optimal monetary policy; commitment; timeless perspective; optimal steady state; staggered price setting; monetary friction; Friedman's rule; Geldpolitik; Zinspolitik; Geldmengensteuerung; Preisrigidität; Theorie